ORGANIZATION OF INTEGRATIVE CARE FOR PATIENTS WITH ONCOPATHOLOGY - G. S. Alekseeva; O. B. Shchitikova (Исследования и практика в медицине)
Clinical testing (providing of integrative care) was conducted to determine the methodology for the treatment and rehabilitation of patients who were previously denied in other hospitals. Defined the methodological approaches to the choice of the treatment, causing minimal harm to patients in other health care organizations were offered only symptomatic or palliative therapy.The purpose of the study:– improvement the quality of life;– increasing the terms of survival;– reduction of depressive state with confirmation of the diagnosis;– reducing the negative effects of the treatment.Patients and methods. In clinical trials 47 patients with stage IV of disease were involved, including in the integrative treatment group was 25 patients (16 women and 9 men), the group standard of treatment, 22 patients (15 women and 7 men). The group consisted of the patients with recurrences of the tumours, and patients after primary treatment at a late stage of the disease. The combination of all possible types of treatment (standard methods of treatment, immune therapy with drug “Helixor®  M”, psychological assistance) was performed depending on the disease defined by the overall clinical picture and psychological readiness of patients to one or another form of therapy. The choice of the injection scheme in order to quickly transition to a maximally tolerated doses was carried out using the control functional state.Results. The use of this method in comparison with the control group showed improvement in the quality of life of patients and increase in terms of survival.Conclusion. The results that are obtained during clinical testing confirmed the positive effect of integrative treatment of patients with oncologic pathology when choosing the best course and combination of treatments, depending on the needs and course of the disease. Also the immunotherapy with drug “Helixor®  M” showed efficacy in the treatment of viral infections for patients with tumors and without them.